Strategi Manajemen Pemasaran Sekolah Berbasis Pendidikan Multikultural di Sekolah Menengah Kejuruan: Strategic School Marketing Management Based on Multicultural Education in Vocational Secondary Schools - Rahmatulloh, Reiga (Risalah Kharisma, 2023)
This study explores the educational marketing management strategy based on multicultural values implemented by a vocational high school in Parigi. The central issue addressed is how the school effectively attracts prospective students amid the challenges of social and cultural diversity within the surrounding community. The purpose of this study is to describe in depth the stages of marketing strategies employed to build institutional appeal and differentiation. This research uses a qualitative approach with a case study method, and data were collected through in-depth interviews, observation, and documentation. The findings reveal that the school’s marketing strategy is structured through eight key stages, including environmental analysis, team formation, unique program offerings, provision of supporting facilities, value-based educational exchanges, strategy execution, market segmentation, and continuous promotion and evaluation. The study concludes that the success of educational marketing lies not only in the quantity of promotion but also in the school’s ability to build values, social engagement, and a multicultural image. The implication is that educational institutions must design adaptive, value-based, and contextually relevant marketing strategies to foster sustainable relationships with the community.